Simultaneous optimisation of stope boundaries and long term production scheduling for production shedules - Little, J.; Topal, Erkan; Knights, P. (Australasian Institute of Mining and Metallurgy, 2011)
Optimisation techniques for underground metalliferous mine design and planning are not commonplace like their open cut counterpart. Optimisation studies which have focused on underground design and planning are amenable to improvement. Additionally, all techniques have ignored the effects that underground design and planning areas have on each other. This means that when optimising an individual area, there is a likelihood of increasing costs or decreasing revenues in areas not included. Considering the interaction and influence key underground design and planning areas have on each other when optimising, will provide more profitable results than if ignored. Optimisation techniques for stope layouts and production scheduling are reviewed. A model that simultaneously optimises stope layouts and production schedules using mixed integer programming is proposed and successfully applied to 64 443 blocks over a 23 year mine life, demonstrating the model’s ability to produce optimal long term mine plans for a sublevel stoping operation with a $22.7m maximised net present value.